Gas chromatographic determination of Amino Acid Enantiomers in tobacco and bottled wines - Hatem, Salama Mohamed Ali; Justus Liebig University Giessen (My University, 2006)
Quantities of free L- and D-amino acids were determined by GC-SIM-MS in twenty five European snuff tobaccos (from Germany, England and Sweden) and eight chewing tobaccos (from the Philippines, Africa and Denmark) and compared to those of cigar, cigarillo, and freshly harvested tobacco leaves of cultivars of Nicotiana tabacum L. Amino acids were isolated from tobacco samples by treatment with 70 % aqueous methanol and purified by a cation exchanger. Next they were converted into their N(O)-pentafluoropropionylamino acid-(2)-propyl esters, and enantiomers separated and quantified by gas chromatography selected ion monitoring mass spectrometry on a Chirasil®-L-Val capillary column. Among L-amino acids the most abundant were Pro, Asx and Glx in the low milligram range (about 2-6 mg/g) whereas the other L- amino acids were in the submilligram range. The D-enantiomers of Ala, Asx and Glx were detected in all samples approaching 34.0 % D-Ala, 13.8 % D-Asx, and 16.1 % D-Glx in different samples. It is assumed that D-amino acids are generated from fructose-L-amino acids (Amadori rearrangement products) which are formed in the course of the Maillard reaction. Wines Quantities of free L- and D-amino acids were determined in twenty six wines, comprising eighteen white wines, two ice wines, four red wines and four sparkling wines. Aim of the study was to investigate whether quantities and pattern of D-amino acids, in particular D-proline, correlates with the time of storage of bottled wines. Besides common wine L-amino acids, varying kinds and quantities of D-amino acids were detected. The most abundant D-amino acids, detectable in all wines, were D-Ala (alanine), D-Asx (sum of aspartic acid and asparagine) and D-Glx (sum of glutamic acid and glutamine). Low relative quantities of 0.3 % - 0.7 % D-Pro were detected in three white wines stored for more than twenty years and did not exceed 0.2 % D-Pro in two red wines stored for ten and twenty years, respectively. An ice-wine stored for 24 years contained 0.9% D-Pro, 6.4% D-Glx, 3.0% D-Asp and 1.5% D-Ala. The data do not provide evidence for a correlation between the age of the bottled wines and quantities of D-amino acids, in particular of D-Pro, determined therein.
Keywords: Aminosäure; Enantiomere; Gaschromatograph; amino acid; Enantiomers; gaschromatography; ddc:640